Recent Advances in Yttrium Iron Garnet Films: Methodologies, Characterization, Properties, Applications, and Bibliometric Analysis for Future Research Directions - Arsad A.Z.; Zuhdi A.W.M.; Ibrahim N.B.; Hannan M.A. (MDPI, 2024)
Due to recent advances in communication systems, dielectric and magnetic ceramics (ferrites) are attractive for use in devices. Spinel-type ferrites were the first material utilized in microwave devices